POSTMAGMATIC ALTERATION IN THE DOLERITE-DIABASE ROCKS ASSOCIATION OF THE NOVOUKRAINKA DYKE FIELD (INGUL TERRAIN OF THE UKRAINIAN SHIELD) - Mitrokhin, A.; Omelchenko, A.; Mytrokhyna, T.; Gatsenko, V.; Vishnevska, E.; Mihalchenko, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The authors have studied some rocks of the Novoukrainka dike field (NDP). The dike rocks were previously identified by them as hypabyssal representatives of Paleoproterozoic dolerite-diabase association (DDA) that is paleoanalogue of continental plateau basalts of the Phanerozoic. The intrusion of the DDA dikes occurred in the time interval between the formation of the Novoukrainka granite complex (2,03-2,04 Ga) and intrusions of anorthosite-rapakivi-granite association of Korsun-Novomirgorod Pluton (1,74-1,76 Ga). It was established that, among the studied dyke rocks besides the usual for DDA cenotypal olivine dolerites and gabbro-dolerites there are their palaeotype counterparts such as diabases and gabbrodiabases. The latter are in varying degrees susceptible to low-temperature postmagmatic alteration. Such changes have a local near fracture nature and occurred at constant volume, ensuring a good preservation of relict structures with broad development of pseudomorphs on the primary igneous minerals. Primary plagioclase, mafic and Fe-Ti-oxide ore minerals exhibit different degrees of resistance to post-magmatic transformations. The ilmenite appears to be most stable that obviously confirms the chemical inertness of titanium and the impossibility of its industrial accumulation during post-magmatic processes of this type. Other rock-forming minerals on the reduction of the degrees of resistance form the following sequence: plagioclase – clinopyroxene – Ti-magnetite – olivine. The most characteristic post-magmatic transformations such as actinolitization of mafic minerals, sericitization and prehnitization of plagioclase were caused due to low-temperature hydrothermal--metasomatic processes. The metasomatism occurred with a noticeable addition of an aqueous fluid and with the removal of Si. At the same time Na and K reveal inert behaviour. These cast doubt on the supposed genetic relationship of the studied post-magmatic changes with the manifestations of the alkali-sodium metasomatism that developed in the region.
Keywords: post-magmatic changes; metasomatism; dike rocks; Ingul Megablock; Ukrainian Shield